The Role of Saudi Environmental Laws and Regulations in Protecting the Environment, and Achieving the goals of sustainability: The Case of Hail City - Albati, Faris Mohammed Abdulmosen; Alsaman, Majed Abdulrhaman Abdullah; Albakjaji, Mohamad (Journal of Ecohumanism, 2024)
Saudi Arabia, a nation rich in natural resources and economic potential, faces significant environmental challenges. Rapid industrialization, urbanization, and a heavy reliance on oil have led to issues such as air and water pollution, desertification, and biodiversity loss. To address these challenges, Saudi Arabia has developed a framework of environmental laws and regulations designed to protect its unique ecosystems and promote sustainable development. In order to apply these rules and regulations locally, many cities and municipalities in Saudi Arabia have adopted initiatives and strategies aiming at applying the national rules. Among these cities is the city of Hail. Hail, a city in north-central Saudi Arabia, is distinguished by its rich history and unique ecological environment. However, the region faces significant environmental challenges, including water scarcity, desertification, and pollution, largely driven by rapid urbanization and agricultural practices. To address these issues, Hail is implementing various initiatives aimed at promoting environmental protection and sustainable development. This essay explores the current state of environmental efforts in Saudi Arabia in general and Hail in particular, supported by practical examples, along with reliable sources for further reading.